"Be Careless with That!" Availability of Product Upgrades Increases Cavalier Behavior toward Possessions. (October 2017) - Bellezza, Silvia; Ackerman, joshua M.; Gino, Francesca
Consumers are often faced with the opportunity to purchase a new, enhanced product, such as a new phone, even though the product they currently own is still fully functional. The authors propose that consumers act more recklessly with their current products when in the presence of appealing, though not yet attained, product upgrades (not just mere replacements). Carelessness and neglect toward currently owned products stem from a desire to justify the attainment of upgrades without appearing wasteful. A series of studies with actual owners of a wide range of different goods (durable, consumable, functional, and hedonic products) and evidence from a real-word data set of lost Apple iPhones demonstrate how the availability of product upgrades increases cavalier behavior toward possessions. Moreover, the authors demonstrate that product neglect in the presence of attractive upgrades can occur without deliberate intentions. Finally, theoretical and managerial implications of these findings are discussed.